STUDI PENGARUH KEPERCAYAAN, KOMITMEN, PENANGANAN KELUHAN DAN FINANSIAL BENEFIT TERHADAP LOYALITAS PELANGGAN GRAB-FOOD DI KOTA SEMARANG - Adhitya Yoga Prasetya; Lukiy (Jurnal Mahasiswa: Jurnal Ilmiah Penalaran dan Penelitian Mahasiswa, 2019)
The purpose of this study was to examine factors in increasing level of customer loyalty. The level customer loyalty is examined from trust, commitment, complaint handling, and financial benefits obtained by consumers. The objects in this study are consumers who use Grab-Food. Data was collected by distributing questionnaires to users of the Grab-Food service. Analysis in this study uses linear regression. The results showed that respondents using Grab-Food who had high loyalty were in productive age. The level consumer loyalty is largely determined by existence high trust, good commitment, improved handling customer complaints and financial benefits transactions made.